Baby Walker: Mother's Knowledge, Injury Prevention Behavior and Incidence of Injury among Toddler in Paseban District, Jakarta - Velmi Revelin; Sri Indiyah Supriyanti (Alma Ata University Press, 2020)
Baby walker is still popularly used by several families, which aims to eneble the child to quickly walk, even though their use might cause injuries. This study aims to determine the relationship of the mother knowledge and prevention behavior toward the injury of baby walker among toddler in Paseban urban village. This study used descriptive corelatif design with applies cross sectional designe. The population are 83 and total sampling is used to take the sample. The sample are 83 responden. The data were analyzed using Chi-Square with p value =0.05 was considered significant. The injury association of baby walker has 47% toodlers, mother's knowledge has 50.6%, mother's who has good prevention behavior are 55.4%, the result of the analysis correlation of mother's knowladge has a p-value = 0.000, mother's prevention behavior has a p-value = 0.000. It can be interpreted that there is a significant relationship among mother's knowladge and prevention behavior toward the injury of baby walker among toddler in Paseban urban village. Based on the results of these studies, improvement of mother knowledge is important in an effort to prevent the occurrence of injury to children who use baby walker by counseling, with good knowledge, mother can prevention behavior on the injury association of baby walker.